The effect of muscle warm-up on voluntary and evoked force-time parameters: A systematic review and meta-analysis with meta-regression - Wilson, C. J.; Nunes, J. P.; Blazevich, A. J. (Journal of Sport and Health Science, 2025)
Background While muscle contractility increases with muscle temperature, there is no consensus on the best warm-up protocol to use before resistance training or sports exercise due to the range of possible warm-up and testing combinations available. Therefore, the objective of the current study was to determine the effects of different warm-up types (active, exercise-based vs. passive) on muscle function tested using different activation methods (voluntary vs. evoked) and performance test criteria (maximum force vs. rate-dependent contractile properties), with consideration of warm-up task specificity (specific vs. non-specific), temperature measurement method (muscle vs. skin), baseline temperatures, and subject-specific variables (training status and sex). Methods A systematic search was conducted in PubMed/MEDLINE, Scopus, Web of Science, Cochrane, Embase, and ProQuest. Random-effects meta-analyses and meta-regressions were used to compute the effect sizes (ES) and 95% confidence intervals (95%CIs) to examine the effects of warm-up type, activation method, performance criterion, subject characteristics, and study design on temperature-related performance enhancement. Results The search yielded 1272 articles, of which 33 met the inclusion criteria (n=921). Increasing temperature positively affected both voluntary (3.7%/°C ± 1.8%/°C (mean ± SD), ES=0.28 (95%CI: 0.14 to 0.41)) and evoked (3.2%/°C ± 1.5%/°C (mean ± SD), ES=0.65 (95%CI: 0.29 to 1.00)) rate-dependent contractile properties (dynamic, fast-velocity force production, and rate of force development (RFD)) but not maximum force production (voluntary: -0.2%/°C ± 0.9%/°C (mean ± SD), ES=0.08 (95%CI: -0.05 to 0.22); evoked: -0.1%/°C ± 0.8%/°C (mean ± SD), ES = -0.20 (95%CI: -0.50 to 0.10)). Active warm-up did not induce greater enhancements in rate-dependent contractile properties (p=0.284), maximum force production (p=0.723), or overall function (pooled, p=0.093) than passive warm-up. Meta-regressions did not reveal a significant effect of study design, temperature measurement method, warm-up task specificity, training status, or sex on the effect of increasing temperature (p>0.05). Conclusion Increasing muscle temperature significantly enhances rate-dependent contractile function (RFD and muscle power) but not maximum force in both evoked and voluntary contractions. In contrast to expectation, no effects of warm-up modality (active vs. passive) or temperature measurement method (muscle vs. skin) were detected, although insufficient data prevented robust sub-group analyses.